Trade Liberalization and Local Development in India: Evidence from Nighttime Lights - Priyaranjan Jha; Karan Talathi (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study the impact of the Indian trade liberalization of 1991 on development at the district level using satellite nighttime lights per capita as a proxy for development. We find that on average trade liberalization increased nighttime lights per capita but there was considerable heterogeneity in the effect. In particular, districts in states with flexible labor laws, districts with better road networks, proximity to the coast, or higher female labor force participation rate seem to have benefited more than other districts.
Keywords: F13; F14; O11; O24; 330; trade liberalization; nighttime lights; per capita income; tariffs; labor laws